Taxonomic position of hake, Merluccius polylepis Ginsburg, 1954, from the Falkland Islands and Tierra del Fuego Region - A. Wysokiński (Acta Ichthyologica et Piscatoria, 1974)
The combined biological and fisheries investigations carried out from the Polish research vessel "Profesor Siedlecki" on the Argentine shelf resulted, among other things, in establishing the large-size hake occurrence that had not been observed before. The fish meristic characters, presented herein, correspond with those of Merluccius polylepis Ginsburg, 1954 known from the southern coast of Chile. The distribution limit for both the Argentine hakes, M. hubbsi and M. polylepis described is set in the Atlantic Ocean between 47 and 48°S. Taxonomically, M. polylepis to the greatest extent resembles M. australis and M. paradoxus.